Deformation‐Induced Supersaturation in Immiscible Material Systems during High‐Pressure Torsion1 . Issue 4 (19th December 2016) - Kormout, Karoline Sophie; Pippan, Reinhard; Bachmaier, Andrea
Abstract : The review focuses on the supersaturation process of immiscible elements induced by high‐pressure torsion deformation. A variety of investigated material systems offers the systematic analysis of the controlling factors for mechanical intermixing, which are mainly determined by the level of the positive heat of mixing and the deformation behavior. The homogeneity of the deformation process strongly influences the degree of supersaturation. Our results show that the fundamental mixing mechanism during deformation is not necessarily the same in all systems, but depends also on the strength differences of the phases and accordingly the deformation behavior. Abstract : Severe plastic deformation (SPD)of immiscible composites can result in nanocrystalline single‐phase supersaturated solid solutions or in partially supersaturated nanocomposites, similar as in mechanical alloying. SPD permits a detailed analysis of the underlying deformation and supersaturation phenomena without the inherent problems of mechanical alloying (ill‐defined applied strain, temperature and impurities).